Manajemen Pengelolaan Springkler Irrigation Dengan Menggunakan Pipa Flexibel Pada Taman Di SMK Nasional Malang - Mulyadi, Lalu; Wulandari, Lies Kurniawati; Wijayaningtyas, Maranatha; Sebayang, Nusa; Hardianto, Hardianto (Jurnal ABM Mengabdi, 2025)
This management is a result of community service, a 2022 research project that will be incorporated into community service at Malang National Vocational School. This involves installing sprinkler pipes and nozzles based on the distance and height of the existing plants, using flexible pipes. Because the park is located near a basketball court, the flexible pipes were replaced with permanent pipes for safety. Because our partners are still using manual irrigation, we will be developing an automated system, namely sprinkler irrigation. Surface irrigation is implemented in Indonesia because agricultural land used to have abundant water, while currently, the amount is decreasing. An irrigation system that increases the effectiveness and efficiency of water use is one solution needed to maintain land productivity, one of which is a sprinkler irrigation system. Sprinkler irrigation systems are generally applied to crops with high economic value. This includes determining the layout design of the sprinkler irrigation network, the required capacity of the sprinkler irrigation network, and the appropriate pump type for planning the sprinkler irrigation system. Based on the results of community service activities carried out at SMK Nasional Malang, namely sprinkler irrigation in the park, which produces results, namely the efficiency of garden irrigation water and makes it easier for users, it can be concluded that: the level of user enthusiasm is very high, this is realized by coming to the location on time with a very strong motivation to gain some understanding and insight related to Sprinkler irrigation. The evaluation results show that the increase in air efficiency is very good, namely 50%.